Genetic Analysis of Field Isolates of Infectious Bursal Disease Virus in Iraqi Farms - Jumaa, Rawaa S.; Allawi, Aida B.; Jabbar, Rebah N. (The Iraqi Journal of Veterinary Medicine, 2020)
Sixty samples of bursa of Fabricius were collected from broiler chickens suspected to be infected with infectious bursal disease virus (IBDV) in different areas of Iraq for molecular evaluation. The extracted nucleic acid was amplified using reverse transcriptase polymerase chain reaction (RT-PCR) targeting genes of segment A (Vp2, Vp3, Vp4 and Vp5 genes) and segment B (VP1 genes). The products of amplification were sent to Korea for sequencing using Sanger method. The sequencing analysis of the IBDV from the Iraqi isolates revealed that each gene had different transition and transversion (nonsense and missense of point mutation) compared to reference genes. The phylogenetic tree analysis showed that the VP2 of segment A of the Iraqi samples was similar to that of an Egyptian strain with 96%similarity, the polypeptide VP2-3-4 of segment A of the Iraqi samples was similar to those of a Chinese strain with 99% similarity and the VP5 of segment A was similar to that of Chinese strain with 99% similarity. However, the phylogenetic tree analysis showed that the VP1 of segment B had 95% similarity with that of a Chinese strain.